2011
DOI: 10.1038/ejcn.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative nutrition is still a surgical orphan: results of a Swiss–Austrian survey

Abstract: Background/Objectives: There is strong evidence for the beneficial effects of perioperative nutrition in patients undergoing major surgery. We aimed to evaluate implementation of current guidelines in Switzerland and Austria. Subjects/Methods: A survey was conducted in 173 Swiss and Austrian surgical departments. We inquired about nutritional screening, perioperative nutrition and estimated clinical significance. Results: The overall response rate was 55%, having 69% (54/78) responders in Switzerland and 44% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
1
30
1
1
Order By: Relevance
“…In reality, about 30% of hospitals rarely or never assess patients' nutritional status preoperatively as recently published by our group [4]. Our findings are in accordance with a recent European survey showing that only 52% of the interrogated units reported a screening routine [14].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In reality, about 30% of hospitals rarely or never assess patients' nutritional status preoperatively as recently published by our group [4]. Our findings are in accordance with a recent European survey showing that only 52% of the interrogated units reported a screening routine [14].…”
Section: Discussionsupporting
confidence: 94%
“…In general, preoperative nutritional assessment of surgical patients is performed either by surgeons, nurses, or by nutrition specialists [4]. However, there is little information available, whether the application of the NRS is really easy and reproducible in daily clinical practice, and how important the inter-observer variability is between surgeons and nutrition specialists.…”
Section: Introductionmentioning
confidence: 99%
“…30,33,34 Modern nutritional formulas entail however 'pharmacological' effects beyond the mere improvement of patients' nutritional status. 35,36 A distinct attribute of immuneenhancing agents is a modulation of the humoral and cellular immune function, that is, a reduction of SIRS and postoperative infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the three studies on the subject demonstrated that the surgical trainees had an insufficient level of knowledge regarding clinical nutrition (6, 7). Another study, which is the only large-scale study on the current practice of general surgeons with regard to clinical nutrition, surveyed the chairmen of the surgery clinics in Switzerland and Austria regarding the current clinical practice at their centers and demonstrated insufficient implementation of nutrition guidelines (5). The aim of the present study was to screen a broad population of general surgeons in Turkey for the awareness of nutritional principles and their clinical practices, as well as to discuss the influence of some potential factors that may affect their tendencies.…”
Section: Discussionmentioning
confidence: 99%